LAJU PINDAH PANAS DAN MASSA PADA PROSES PENGERINGAN GABAH MENGGUNAKAN ALAT PENGERING TIPE BAK (BATCH DRYER) - Amin, Saiful; Jamaluddin P, Jamaluddin P; Rais, Muhammad (Jurnal Pendidikan Teknologi Pertanian, 2018)
This study aims to determine the mechanism of heat transfer and mass on the drying process of grain that uses hot air as a medium of heat conduction. This research is a type of experimental research consisting of two variables namely variable A and variable B. Variable A is a temperature with three levels. They are 40, 50 and 60 Â°C. While variable B is the thickness of the stock with three levels. They are 5, 10 and 15 cm. The sample is wet grain which is dried using a batch dryer. Its initial moisture content is 20,5 %. To determine the temperature changes that occur during the drying process, the researcher measured the air temperature by using a thermometer. The measurement was carried out before and after drying by measuring the moisture content to determine the changes of grain water level of each treatment used. The result showed that the higher the temperature and the reduction of the pile of materials used, the higher the heat transfer rate and the greater mass transfer. So, it causes the grain water content to decrease